Time spent cycling, walking, running, standing and sedentary: a cross-sectional analysis of accelerometer-data from 1670 adults in the Copenhagen City Heart Study - Melker Staffan Johansson; Mette Korshøj; Peter Schnohr; Jacob Louis Marott; Eva Irene Bossano Prescott; Karen Søgaard; Andreas Holtermann (BMC, 2019)
Abstract Background Information about how much time adults spend cycling, walking and running can be used for planning and evaluating initiatives for active, healthy societies. The objectives of this study were to describe how much time adult Copenhageners cycle, walk, run, stand and spend sedentary using accelerometers, and to describe differences between population groups. Methods In the fifth examination of the Copenhagen City Heart Study, 2335 individuals gave consent to wear accelerometers (skin-attached; right thigh and iliac crest; 24 h/day, 7 consecutive days) of which 1670 fulfilled our inclusion criteria (≥16 h/day for ≥5 days; median wear time: 23.8 h/day). Daily time spent cycling, walking, running, standing and sedentary was derived from accelerometer-based data using the Acti4 software, and differences between sex, age groups, level of education and BMI were investigated using Kruskal-Wallis rank sum tests. Results Among those cycling (61%), the median cycling time was 8.3 min/day. The median time walking, running, standing and sedentary was 82.6, 0.1, 182.5 and 579.1 min/day, respectively. About 88% walked fast (i.e., ≥100 steps/min) ≥30 min/day. The shortest duration and lowest prevalence of cycling, walking and running were found among older individuals, those with a low level of education, and individuals being overweight or obese. Conclusions We found a long duration and high prevalence of cycling and walking, but also that many adult Copenhageners spent much time sedentary. Population groups with low participation in physical activities such as cycling and walking should be targeted in future initiatives towards an active, healthy society.